Socialization of Charcoal Briquette Making and Application of Briquette Mixing and Printing Machines at Suwarno MSMEs, Kediri, East Java: SOSIALISASI PEMBUATAN BRIKET ARANG SERTA PENGAPLIKASIAN MESIN PENGADUK DAN PENCETAK BRIKET PADA UMKM SUWARNO KEDIRI JAWA TIMUR - ZULFA KHALIDA; Hadi Rahmad; Eti Cahyanti; Wiwik Mukholafatul; Rima Zidni K.N; Very Verdiansyah; Mosa Inam; Leontri Ariwidiansyah; Dyno Arga (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: this community service is aimed to increase charcoal production by converting unused charcoal fragments into briquettes and also training how to use and maintain the briquette machine, how to make attractive product packaging and how to market product on social media. Research Methodology: This community service includes three stages, those are the socialization of making briquettes by using briquette machine, socialization of machine maintenance and socialization of packaging and marketing product. Results: Based on the results of testing the briquette machine, machine works on good performance and the efficiency increases up to 20% of the initial planned capacity. The results showed an increasing of turnover around 50-100 kg (20-40%) each day. Conclusion: Based on the evaluation results, there is an increasing production capacity and the products can be packaged properly. Limitation: The process of breaking down the charcoal into smaller granules for subsequent processing still requires a manual crusher, which takes longer to make briquettes. Contribution: This briquette machine can provide solution for making briquettes more efficiently. Furthermore, this briquette machine can also be used for larger briquette production by adjusting the machine capacity.